Managing My White Fragility (It's Not About Me) (International Journal of Multidisciplinary Perspectives in Higher Education, 2021)
White privilege, white fragility, and white systems of oppression, both in the workplace and in everyday life, function to cause white people desiring a more just society to stumble, even when they’re aware of these obstacles. In this essay, I discuss my experiences, during the dual pandemics of 2020, in trying to manage my white privilege and my white fragility when thrust into a role for which I felt I was not qualified—teaching Culturally Relevant Pedagogy and Classroom Management—alongside a Black colleague who is an expert in social justice education. Contextualized partly in the police killings of Black people, I explore how white people like myself need to work consciously to always humanize people of color, especially when claiming racial justice allyship.